Sustainable Development Status of Zakat Recipients: Empirical Investigation Based on Malaysia’s Kedah State - Alam, Md Mahmudul; Abd. Wahab, Norazlina; Al Haq, M Ashraf; Ahmad, Siti Aznor (Inderscience Publishers, 2021)
Zakat is compulsory charity in Islam to fight poverty and inequality, but there is a gap in literature concerning the performance of zakat in terms of achieving sustainable development for its recipients. Therefore, this study intends to assess the role of zakat in achieving the sustainable development status for recipients. This study collected primary data through a questionnaire survey among 440 zakat recipients from the Kedah State in Malaysia. The data were analysed using structural equation modelling. The findings reveal that zakat helps to improve the overall sustainable development status of its recipients, but the economic aspect improves more than the social and environmental aspects. Therefore, to ensure the success of zakat in line with the goals of achieving sustainable development for recipients as advocated by the United Nations, the policymakers and zakat administrators around the world and particularly in Malaysia need to focus on redesigning the zakat management program